Polychaetes from red mangrove (Rhizophora mangle) and their relationship with the water conditions in the Gulf of Urabá, Colombian Caribbean (2016)
ABSTRACT : Polychaetes play a significant role in benthic communities’ ecology; they dominate the infauna, recycle nutrients from the water column and are commonly used as biological indicators. Along the Gulf of Urabá (Colombian Caribbean), particularly for the zones of the Marirrío Bay and the Rionegro Cove, there are no reports about ecological aspects of polychaete species; only a few taxonomic studies have been conducted. In this research we evaluate the relationship between polychaete species associated with red mangrove roots, Rhizophora mangle, and some physicochemical variables of the water column; also, we made some notes about the spatial distributions of polychaetes species within the two study areas. We found that the environmental variables that best explain polychaetes community segregation are the dissolved oxygen and electrical conductivity; temperature seems to have not a significant effect. In terms of spatial distribution, we found that Alitta succinea, Capitella cf. capitata and Ficopomatus miamiensis occupied the inner, middle and outer zones for both study area and seasons, while Stenoninereis sp. 1 (rainy and dry season) and the exotic polychaete Ficopomatus uschakovi (rainy season) were found just in Rionegro Cove. Finally, the species Nicolea modesta is registered by first time for the Gulf of Urabá, Colombian Caribbean.